Improved gas diffusion within microchanneled cathode supports of SOECs for steam electrolysis - Dong, D.; Shao, X.; Hu, X.; Chen, K.; Xie, K.; Yu, L.; Ye, Z.; Yang, P.; Parkinson, G.; Li, Chun-Zhu (Elsevier Ltd, 2016)
Gas diffusion limitation within Ni/YSZ cathode supports of solid oxide electrolysis cells (SOECs) during steam electrolysis has been reported in previous studies. In this study, a microchanneled cathode support has been prepared by a mesh-templating phase-inversion process to improve the gas diffusion. Numerous channels with one end open on the cathode surface cross the support and are stopped on the other side of the support by a porous layer which acts as a cathode functional layer. The integrated structure is ideal for achieving both fast gas diffusion and a long three-phase-boundary for performing the cathode reactions. Compared with conventional cathode supports, the microchanneled cathode support produced higher current densities at low steam concentrations of feed gas during steam electrolysis, which is attributed to the fast gas diffusion achieved within the channels. Therefore, the microchannel structure of cathode supports can increase hydrogen yield and steam utilization efficiency.